Developing an experiment-based inquiry model to enhance students’ creativity in writing - Ambarita, Rosmita; Pohan, Jusrin (Universitas Islam Sultan Agung, 2025)
The ultimate goal of learning writing skills in language education is for students to produce their own written work. Students are not merely passive recipients of writing instruction but active participants in the writing process. However, in practice, many students struggle to write different types of texts, such as argumentative, narrative, expository, and persuasive essays. This issue persists in writing education, as students often understand writing rules theoretically but face difficulties in applying them practically. The main objective of this research is to develop an inquiry-experiment model for teaching writing in high school. This research involved a research and development approach using the Plomp model, which consisted of the prototype stage, development stage, and evaluation stage. Throughout these stages, the design of student books, teacher books, and model books was carried out. The instruments used in this study included validation questionnaires, practicality questionnaires, effectiveness questionnaires, observation guidelines, and interview guidelines. The sampling technique was carried out by purposive sampling by determining characteristics that are appropriate to the research objectives and problems. The sample for this research consisted of 40 students who were used as trials for the model developed. The data analysis technique carried out two activities, namely qualitatively and quantitatively. The results of this research show that the experimental-based inquiry learning model can make students creative in writing as seen from the results of students' writing which has varied according to the rules of good and correct writing. Apart from that, students' soft skills have increased, seen in communication and collaboration.